Strang Splitting Method for Burgers-Huxley Equation - Çiçek, Yeşim; Tanoğlu, Gamze; Tanoğlu, Gamze (Elsevier Ltd., 2016)
We derive an analytical approach to the Strang splitting method for the Burgers-Huxley equation (BHE) ut+αuux-ε uXX=β(1-u)(u-γ)u. We proved that Srtang splitting method has a second order convergence in Hs(R), where Hs(R) is the Sobolev space and s is an arbitrary nonnegative integer. We numerically solve the BHE by Strang splitting method and compare the results with the reference solution.
Keywords: Error analysis; Operator splitting methods; Regularity; Sobolev spaces; Burgers-Huxley equation